Online Criminal Case Trials from A Normative Perspective and Substantive Justice - Aziza Azra Larissa; Muchamad Iksan (Proceeding International Conference Restructuring and Transforming Law, 2023)
In 2020, the Covid19 pandemic outbreak has affected not only Indonesia but has contaminated all countries throughout the world and has had an impact on all aspects of life, including the judicial aspect or the legal services of judicial institutions. This situation also forced the Supreme Court to move to implement policies to realize official duties from home, which also applies to judges and court officials. Due to the dire situation, courts which are generally held conventionally have shifted to online justice, i.e. carried out over long distances. This research article applies normative juridical research methods by examining library materials, namely primary and secondary legal materials. The data collection technique uses library research, by collecting data and information or legal materials related to the substance of the research. After the legal materials are collected, analysis is carried out and appropriate conclusions are drawn regarding the problems contained in the problem formulation. This research applies data analysis techniques using deductive logic. This conclusion is based on an analysis of the problems of online trials viewed from a normative legal perspective accompanied by the rules.This online trial is clear evidence of the Supreme Court's responsibility to the public to provide fast, simple and accurate services without delaying or hindering the public in achieving benefits and access to justice. Because, for the Supreme Court "Justice Delayed, Justice Denied" means that if justice is delayed, there is no justice.